Performance of the Mojokerto City Communication and Informatics Office in Handling Public Complaints through the Digital Platform â€œCurhat Ning Itaâ€ - Roihana Nuria Husna; Eva Hany Fanida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of information technology has encouraged local goverments to introduce digital based public service innovations to improve the effectiveness of communication between the government and the community. One such innovation is the Curhat Ning Ita platform managed by the Communication and Informatics Office of Mojokerto City as an online channel for public complaints. Through this platform, citizens can submit complaints, aspirations, and reports related to public services more easily, quickly, and efficiently. However, in its implementation, several challenges remain, including delays in providing responses and a lack of clarity regarding the follow up of reports submitted by the public. This study aims to analyze the performance of the Communication an Informatics Office Of Mojokerto City in handling public complaints through the Curhat Ning Ita platform. This research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving the administrators of the Curhat Ning Ita service at the Communication and Informatics Office of Mojokerto City as well community members who use the service. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing.The results show that the performance of the Communication and Informatics Office of Mojokerto City in handling public complaints through the Curhat Ning Ita Platform has generally been fairly good. This can be seen from the ease of access to the service, the responses provided to public reports, and coordination efforts with related agencies in following up the complaints. Nevertheless, several aspects still need improvement, particularly regarding the consistency of response time, the clarity of information regarding the progress of complaint handling, and the strengthening of coordination among related agencies.